Distribution of PKH Funds as a Form of Government Service for Poor Families - Aulia Rahma Mootalu; Rusli Isa; Yacob Noho Nani (Public Policy Journal, 2026)
This study aims to find out how effective the distribution of funds from the Family Hope Program (PKH) is in improving the welfare of beneficiaries in Saibuah Village, Posiga District, South Bolaang Mongondow Regency, North Sulawesi Province. The main subfocus of this study includes four aspects of measuring effectiveness, namely: (1) Accuracy of Program Targets, (2) Program Socialization, (3) Program Objectives, and (4) Program Monitoring. This research uses a qualitative, descriptive approach. Data collection techniques are carried out through interviews, observations, and documentation. The results of the study show that the distribution of funds for the Family Hope Program (PKH) in Saibuah Village has not been fully running optimally. In terms of the accuracy of program targets, most of the beneficiaries have met the set criteria, but there are still people who should be eligible to receive assistance but have not been recorded as beneficiaries. In the aspect of program socialization, PKH assistants and village governments have socialized to the community through meetings of beneficiary groups, although there are still people who do not fully understand the mechanisms and obligations in the program. In terms of program objectives, PKH assistance is considered to be able to help ease the economic burden on beneficiary families, especially in meeting education and health needs. However, this program has not been able to significantly improve the welfare of the community. Meanwhile, in the aspect of program monitoring, PKH companions routinely supervise and evaluate beneficiaries through group meetings and direct visits to beneficiaries' homes. Overall, the PKH program provides benefits to the community, but improvements are still needed in terms of data collection, socialization, and monitoring so that the program can run more effectively.